2018
DOI: 10.21608/mjcu.2018.60290
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Repair of Pediatric Inguinal Hernia by Disconnection of the Hernial Sac

Abstract: Background: Several techniques are used for laparoscopic treatment of pediatric inguinal hernia (PIH). Disconnection and peritoneal closure was described by Becmeur in 2004, as an effective technique mimicing open technique. Others described disconnection only as an effective laparoscopic treatment of PIH specially for small defects. Here in, we describe the short term results of laparoscopic disconnection only of the hernial sac.Patients and Methods: This prospective clinical study was carried out in the Pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Lee et al (13) stated that treatment of children inguinal hernias by laparoscopic purse-string suture of the internal inguinal opening of the hernia sac has shown to be a safe, effective, and reliable approach. Moreover, Mohammad et al (14) demonstrated that patients could drink fluids orally 2 to 3 hours following surgery. Everyone got a 15mg/kg/dose dosage of paracetamol intravenously.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al (13) stated that treatment of children inguinal hernias by laparoscopic purse-string suture of the internal inguinal opening of the hernia sac has shown to be a safe, effective, and reliable approach. Moreover, Mohammad et al (14) demonstrated that patients could drink fluids orally 2 to 3 hours following surgery. Everyone got a 15mg/kg/dose dosage of paracetamol intravenously.…”
Section: Discussionmentioning
confidence: 99%